Effects of bentonite binder dosage on the properties of green limestone pellets - Jovanović Vladimir D. (Hemijska Industrija, 2017)
This paper presents the results of tests carried out to determine how the dosage of bentonite added as binder, affects the properties of green pellets made of the limestone fines that originate from Lithothamnium limestone processing. Bentonite was added to limestone in different mass fractions (1, 2.5, 5 and 10%), whereas all the other parameters of the pelletizing process remained constant. The aim of pelletizing was to consolidate limestone fines and form mechanically stable pellets, provided that all the other properties of limestone remain unchanged. The pellets formed in this way were analysed applying DTA/TG analysis and FTIR and SEM analyses. The results showed uniform distribution of bentonite in the pellets, demonstrated that the pellets are compact and there is no formation of new compounds. The pellets were tested for resistance to impact, compressive strength and abrasion resistance. Also disintegration tests were performed to determine the time required for the pellet to disintegrate completely in water. These mechanical properties are essential for transport, handling, storage and general use of pellets. The values of most of the parameters established for pellets with 5% bentonite, meet the standards required for use in agriculture for liming acid soils, however their application is limited because their impact resistance is unsatisfactory and the time required for their complete disintegration in water is extremely short. It should be noted that further increase of bentonite content (over 10%) will not improve the quality of green pellets. In view of the results obtained, it is necessary to introduce drying into the pelletizing process in order to bring the green pellets into solid state. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR-34013]